AN ANALYSIS OF ILLOCUTIONARY AND PERLOCUTIONARY ACT OF DIRECTIVES UTTERANCE USED IN DIGITAL STORYTELLING OF LITTLE RED RIDING HOOD - Fristi Arfiawati (Jurnal Sastra - Studi Ilmiah Sastra, 2021)
The research which is entitled An Analysis of Illocutionary and Perlocutionary Act of Directives Utterance Used in Digital Storytelling of Little Red Riding Hood focused on analyzing the Illocutionary and the perlocutionary act based on the theory of Austin and Searle. The method of this research is descriptive qualitative and the data taken is utterances from digital storytelling video. The writer transcribed utterances from the written form and analyzed by applying the theory of speech acts. The writer found 8 directives utterances which comprises into three asking acts, one ordering acts, three advising acts, and one requesting acts. Furthermore, the result showed that the illocutionary act of directives utterances of Little Red Riding Hood has some intention in making an utterance (implied meaning), and perlocutionary act shows the effect of the utterance.